Engineering the nanostructures of solution proceed In2SexS3−x films with enhanced near-infrared absorption for photoelectrochemical water splitting. (27th October 2022) - Liu, Baoze; Chu, Wenlong; Liu, Siyu; Zhou, Yajiao; Zou, Luwei; Fu, Junwei; Liu, Min; Fu, Xuewen; Ouyang, Fangping; Zhou, Yu
Abstract: Two-dimensional (2D) materials have been utilized for the photoelectrochemical (PEC) production of hydrogen by water splitting, however the reaction performance of which is limited by thermodynamic protons adsorptions, the specific materials solar absorption spectrum, materials carrier mobility and lifetime. Here, we report a facile solution processed method for the synthesis of 2D In2 Se x S3− x alloy films, in which the obvious crystalline to amorphous transition was observed as the annealing temperature decreased from 400 °C to 80 °C. Different porous nanostructures of the films have been created by the temperature controls, showing over 200% absorption in the near-infrared range for the sample that annealed at 400 °C than the other samples. The transient absorption measurements of crystalline samples are clearly shown the carrier lifetime is dramatically improved than the amorphous samples, which are critical to the hydrogen evolution performance. Finally, the PEC water splitting performances have been measured to discuss the structure-properties relations, showing the overpotentials reduction of over 100 mV for enhanced near-infrared absorption samples. This work clearly gives out the optical structure and crystal structure design strategy for improving the PEC performance.